Inkarnasi Menurut Hilarion Alfeyev: Tindakan Kasih Allah Dalam Memperbaiki dan Memulihkan Kodrat Manusia - Syutriska Gulo; Hendi Wijaya (JURNAL TRANSFORMASI: Jurnal Teologi dan Kepemimpinan, 2023)
The doctrine of incarnation is no longer a new topic of discussion. Incarnation has been a never-ending discussion in the history of Christianity because it is closely related to God, who is worshiped and glorified. This article examines this incarnation based on Hilarion Alfeyef's understanding. The method used in writing is based on a literature method from the book "Orthodox Christianity" by Hilarion Alfeyev. This writing was also supported by church fathers, books, and theological journals related to the discussion. Alfeyev emphasizes that the incarnation of the Word of God is an act of God's love in repairing and restoring human nature that has been damaged. Other scholars claim that God became incarnate in punishing human sin. However, this is behind this statement. Alfeyev found God's act of love to be the main reason for the incarnation, not human sin. Therefore, the carnation is an integral part of human life. The results of this article found that God's act of love made man back into his image and likeness through restoration in the Incarnation of the Word of God.